(untitled) (Bangladesh Journal of Agricultural Research, 2015)
The research work was carried out at the Seed Laboratory of Agronomy Department of Bangladesh Agricultural University, Mymensingh, Bangladesh during the period from March to November in 2008 to find out the effect of different osmopriming techniques on seedling emergence of maize. Seventeen osmopriming techniques viz., T1 = 1% Na2SO4, T2 = 3% Na2SO4, T3 = 5% Na2SO4, T4 = 1% K2HPO4, T5 = 3% K2HPO4, T6 = 5% K2HPO4, T7 = 1% ZnSO4, T8 = 3% ZnSO4, T9 = 5% ZnSO4, T10 = 1% Ca(H2PO4)2, T11 = 3% Ca(H2PO4)2, T12 = 5% Ca(H2PO4)2, T13 = 1% H2O2, T14 = 3% H2O2, T15 = 5% H2O2, T16 = Hydropriming, T17 = Non-priming (control) were used as experimental variables. Different osmopriming methods on seedling emergence performance of maize was evaluated at two moisture levels viz., 30 and 60% moisture of saturated sand in the experiment. Germination percentage, germination index and mean germination time were influenced significantly by osmopriming methods. Seed priming with 3% ZnSO4 showed the highest seedling emergence which was followed by 1% H2O2 and 3% Ca (H2PO4)2. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21986 Bangladesh J. Agril. Res. 39(3): 427-435, September 2014